The Energy Conservation Strategies Can Improve Self Care Management of Chronic Kidney Disease Patients with Hemodialysis - Nieniek Ritianingsih; Nawati Nawati; Farial Nurhayati (Indonesian Journal of Global Health Research, 2023)
Chronic Kidney Disease (CKD) is one of the health problems in the world, with a prevalence of around 13.4% (11.7-15.1%), and end-stage kidney disease (ESKD) patients who require kidney transplant therapy are around 4,902 to 7,083 million. One of the treatments for CKD is hemodialysis. Hemodialysis is a treatment action performed on CKD patients in order to survive. However, these actions have side effects on the physical and psychological conditions of patients with CKD. To prevent the more severe impact of hemodialysis, CKD patients on hemodialysis require self care management including: diet monitoring, stress management, safe activities, good lifestyle, and medication monitoring. Self care management of CKD patients can be improved through the implementation of energy conservation strategies. Through this strategy, the patient will be empowered to be independent when carrying out their daily activities by carrying out the energy saving process, with prior teaching on the implementation of the energy conservation strategy itself. This study aims to knowing the effect of implementing energy conservation strategies on self care management of patients with chronic kidney disease with hemodialysis in the intervention group and the control group. This research is a quantitative research that uses a quasi-experimental method with a pre-test-post-test control group design approach. The number of samples was 32 people in the intervention group and 32 people in the control group. The type of bivariate analysis used is the dependent sample test (Paired t-test) and the independent t-test. Statistical test results obtained a p value of 0.010, it can be concluded that there is a significant difference between the value of self care management in the control group and the value of self care management in the intervention group after the energy conservation strategy was implemented.